(untitled) (Annals of Medical Research, 2023)
Aim: Maternal hypotension caused by extensive sympathetic blockade is a serious complication of spinal anesthesia during cesarean section. This study planned to determine the relationship between weight, height, BMI, abdominal circumference (AC), hip circumference (HC), and AC-to-hip ratio with the ephedrine consumption in patients who underwent cesarean section with subarachnoid block. Materials and Methods: The study population comprised 60 women. Prior to spinal anesthesia; patients’ demographic characteristics (age, weight, height), abdominal and hip circumferences, basal hemodynamic parameters, and ASA physical status were recorded. To minimize errors, three consecutive measurements were obtained; results were averaged and the AC-to-hip ratio was calculated by dividing the values of the abdominal (cm) and hip circumference (cm). In all patients, spinal anesthesia was done in the sitting position using 2.4 ml 0.5% hyperbaric bupivacaine (12 mg). Persistent hypotension was treated with intravenous ephedrine (5 mg). The number of patients who used ephedrine and the total amount of ephedrine used during surgery were recorded. Results: Of these 60 participants, 40 (66.6%) patients had hypotension requiring ephedrine administration. There is a positive correlation between ephedrine consumption (mg) and abdominal circumferences (r=0.280, p=0.03). Also, there is a significant positive correlation between ephedrine consumption (mg) and AC-to-hip ratio (r=0.608, p<0.001). The correlation coefficient between the ephedrine dose with the AC-to-hip ratio was 56.805, the p-value was <0.001 and AC was 0.211, with a p-value of 0.030 which means the correlation was statistically significant. Conclusion: Abdominal circumference and AC-to-hip ratio have a significant correlation with ephedrine consumption in patients who underwent cesarean section via subarachnoid block with a given dose of 2.4 ml 0.5% hyperbaric bupivacaine.